Pengaruh Literasi Keuangan, Pendapatan, Kontrol Diri dan Teknologi Finansial terhadap Perilaku Pengelolaan Keuangan Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Ponorogo - Putri Rismawati, Adelia; Zulfa Wafirotin, Khusnatul; Firdausi Mustoffa, Ardyan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of financial literacy, income, self-control, and financial technology on the financial management behavior of students at the Faculty of Economics, Universitas Muhammadiyah Ponorogo. This research employed a quantitative descriptive approach. The population consisted of 982 active students, with a sample of 100 respondents selected using purposive sampling and proportionate stratified random sampling techniques. Data were collected through a questionnaire measured using a Likert scale and analyzed using multiple linear regression with SPSS version 25. The results indicate that financial literacy and income have a significant effect on financial management behavior, whereas self-control does not have a significant effect on financial management behavior. Simultaneously, financial literacy, income, self-control, and financial technology have a significant effect on students' financial management behavior. The Adjusted R Square value of 0.440 indicates that these four variables explain 44% of the variation in financial management behavior.